Stillborn Banking Union: Explaining Ineffective European Union Bank Resolution Rules. (8th June 2021) - Asimakopoulos, Ioannis; Howarth, David
Abstract: Our contribution demonstrates and explains the ineffectiveness of European Union (EU) bank resolution rules, a core element of Banking Union. This inadequacy owes in large part to the limited access to and insufficient availability of EU resolution funds and inadequate national deposit guarantee schemes in most EU member states, in conjunction with the relatively high minimum requirements for own funds and eligible liabilities (MREL) for many EU banks. In many cases, these requirements are unlikely ever to be met – particularly for retail banks most likely to require resolution in the euro periphery. We offer a liberal intergovernmentalist analysis to explain the inadequacy of the EU resolution regime by examining German and French government preferences on EU rules on bank capital requirements agreed earlier in 2013 and national deposit guarantee schemes agreed in 2014. These government preferences were shaped significantly by the preferences of national banks and bank associations.